Dynamics of Sedimentation Process at Riko River Estuary, Balikpapan Bay - Soeyanto, Endro; Arifiyana, Arifiyana (Oseanologi dan Limnologi di Indonesia, 2018)
Development of the marine facilities (i.e. port, workshops, laboratories, etc)  for Indonesian Research Vessels and National Center for Marine Research in the proposed National Science Technopark (NSTP) Maritime Region at District of Penajam Paser Utara, East Kalimantan Province, needs to understanding the dynamic of waters physical environment. Due to the NSTP-Maritime region located at Riko River as part of Balikpapan Bay waters, it needs an ocean interaction study between open sea (Balikpapan Bay) and Riko River waters. This study used a 2D-Hydrodynamic Model  for  Riko River and Balikpapan Bay waters and adjacent sea. The model simulated the hydrodynamic conditions on the waters and   furthermore predicted   the mud transport in  September - November 2016 using the river flow and total suspended sediment data collected in November 2016. The model results showed that the average of sediment load movement due to the dynamic of waters at the estuary is   ± 4,25 x10-3 kg per second or ± 367,7 kg per day. This preliminary study hopefully  can explain the shallowing  processes in mouth of Riko River.